A modern scientific perspective on the flavor and functional properties of diverse teas in traditional cuisine “tea-flavored fish”: From macroscopic quality to microscopic variations - Wenxia Wang; Kun Liu; Chunlong Liu; Bei Yang; Hao Dong; Wenzhen Liao; Xingfen Yang; Qi He (Food Chemistry: X)
The historical appreciation of tea dates back to ancient times, while technological limitations have long hindered in-depth exploration of its flavor complexity and functional attributes. This study investigated the effects of various teas on a traditional delicacy, “tea-flavored fish”, using teas processed via traditional methods. Analysis of functional components revealed that processing and fermentation reduced catechin levels (186.3 mg/g to 58.8 mg/g) while increasing theaflavins (16.6 mg/g to 39.6 mg/g), leading to decreased antioxidant and antimicrobial activities. Tea flavored fish was prepared following traditional techniques. The results indicated that the teas preserved their sensory qualities such as texture and color, inhibited metabolic activity and microbial growth, delayed lipid oxidation and protein degradation, and inhibited biogenic amine accumulation. Furthermore, minor compositional variations were observed in the final product. These findings offer novel insights into the application of modern scientific concepts to elucidate the principles underlying traditional craftsmanship.